Synthesis of Double-Bond-Substituted Hemithioindigo Photoswitches - Gerwien, Aaron; Reinhardt, Till; Mayer, Peter; Dube, Henry (Organic Letters, 2018)
A very short, high yielding, and convergent synthesis with broad substrate scope, enabling access to a very diverse range of hemithioindigos with 4-fold substituted double-bonds, is presented. With this method, carbon as well as nitrogen, oxygen, or sulfur based substituents can easily be introduced, delivering a wide array of novel structural motifs. Irradiation studies with visible light demonstrate proficient photoswitching properties of these chromophores at wavelengths up to 625 nm.
CRIS-Team Scopus Importer:2020-04-02